The complete guide to religious education volunteers - Ratcliff, Donald; Neff, Blake J.; Burgess, Harold William; Lee, James Michael (Birmingham, AL Religious Education, 1993)
Includes bibliographical references and indexes.
Keywords: Voluntarism -- religious aspects -- Christianity; Christian education